(untitled) (Bioscience Journal, 2018)
This study aimed to evaluate the decomposition and nutrient release from residues of the culture of oats and fallow inÂ crop-livestock integration system. The experimental design was a randomized complete block design with two replications, as parcels being formed by four managements (fallow, oats without grazing, oats grazed once and twice), and the subplots for evaluation periods along the soybean crop in succession (0, 10, 20, 30, 50, 100 and 120 days after sowing). The residual amounts of dry matter and the contents of Carbon (C), Nitrogen (N), Phosphorus (P) and Potassium (K) were determined. Oats without grazing and fallow with natural reappearance of turnip + ryegrass were the treatments that presented the highest amount of dry matter remaining, reaching 5,219 and 6,781 kg ha-1, respectively. The amount of nutrients, N, P and K released from the residues, were similar independent from the management adopted, with exponential reduction proportional to the reduction of the remaining dry matter. K was the nutrient released faster from the residues and should be considered at the time of fertilization calculation of the culture to be implanted. The integrated crop-livestock system in which takes place one and two grazing oats, even reducing soil cover, enables high nutrient cycling.